2016
DOI: 10.15185/izawol.306
|View full text |Cite
|
Sign up to set email alerts
|

Do schooling reforms improve long-term health?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several studies find an association between higher education and better health (see Madden, 2016) and improved mental health (e.g. Bauldry, 2015;Chevalier and Feinstein, 2007).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Several studies find an association between higher education and better health (see Madden, 2016) and improved mental health (e.g. Bauldry, 2015;Chevalier and Feinstein, 2007).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Other studies find associations between nutritional status, adiposity, and physical activity and rates of depression (Ngasa et al, 2017;Li et al, 2018;Jin et al, 2019). A large body of research has found that education (Bauldry, 2015;Madden, 2016) and religiosity (Wangmo and Teaster, 2010;Gearing and Alonzo, 2018) are protective against depression, which would suggest that monastics may be relatively buffered from experiencing depression. However, another study of Tibetan refugees living in India found lower prevalence of depression and importantly found no association between monastic status or educational variables and depression levels (Sachs et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Monastics may experience lifestyle factors that put them more at risk for depression, a possibility that warrants further inquiry. Large bodies of research have found that education (48,49) and religiosity (50,51) are protective against depression, which would suggest that monastics may be relatively buffered from experiencing depression. However, another study of Tibetan refugees living in India found lower prevalence of depression and importantly found no association between monastic status or educational variables and depression levels (52).…”
Section: Discussionmentioning
confidence: 99%